2007
DOI: 10.1002/ana.21113
|View full text |Cite
|
Sign up to set email alerts
|

Imaging correlates of axonal swelling in chronic multiple sclerosis brains

Abstract: Axonal swelling and axonal loss were major pathological features that distinguish T2T1MTR regions from T2-only regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
113
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 47 publications
8
113
1
1
Order By: Relevance
“…Such technologic advancements offer unprecedented resolution of micron-sized axons (12,16) in the living human brain. We hypothesized that MS lesions on high-gradient-diffusion MR images obtained by using a gradient strength of up to 300 mT/m would show decreased axon density and increased axon diameter, as has been shown in prior histopathologic studies (17)(18)(19). The purpose of this study was to evaluate the ability of high-gradient-diffusion MR imaging using gradient strengths of up to 300 mT/m to characterize axonal disease in lesions and normal-appearing white matter (NAWM) in patients …”
Section: Discussionmentioning
confidence: 95%
“…Such technologic advancements offer unprecedented resolution of micron-sized axons (12,16) in the living human brain. We hypothesized that MS lesions on high-gradient-diffusion MR images obtained by using a gradient strength of up to 300 mT/m would show decreased axon density and increased axon diameter, as has been shown in prior histopathologic studies (17)(18)(19). The purpose of this study was to evaluate the ability of high-gradient-diffusion MR imaging using gradient strengths of up to 300 mT/m to characterize axonal disease in lesions and normal-appearing white matter (NAWM) in patients …”
Section: Discussionmentioning
confidence: 95%
“…Those that show profound hypointensity and permanence primarily reflect irreversible tissue destruction (i.e., irreversible demyelination and axonal loss) whereas those that are transient reflect edema and demyelination with subsequent remyelination. 21,22 Not surprisingly, chronic persistent T1-hypointense lesions are associated to a moderate degree with global brain atrophy. 23,24 However, there are technical considerations to be kept in mind with regard to T1-hypointense lesions.…”
Section: T1 Hypointense Lesionsmentioning
confidence: 99%
“…31 Profoundly reduced MTR indicates a chronic inactive lesion with axonal swelling, axonal loss, and severe demyelination. 22,89,90 MTI is also capable of revealing microscopic damage in normal appearing brain tissue that is free from any visible lesions on conventional MRI scans. 86,91,92 Many studies have demonstrated MTR changes in NAWM in all the MS phenotypic subtypes, [91][92][93] including patients very early in the course of the disease (FIG.…”
Section: Fig 5 Axial Magnetization Transfer (Mt) Images and Maps Ofmentioning
confidence: 99%
“…Postmortem in situ brain imaging was performed and tissue was processed as described previously. 9 For this study, we analyzed brain MRI and tissue from 7 patients with MS (table).…”
mentioning
confidence: 99%
“…After fixation, the hemisphere was reimaged in a custom-designed polycarbonate slicing box. 9 After postfixation MRI, the brain was sliced (1 cm coronal sections) within the box and photographed. The postmortem T1W MRI was registered to the postfixation MRI using rigid-body followed by affine transformations with FLIRT 10 ; in 4 of the cases, additional nonlinear registration was performed using FNIRT (http://www.…”
mentioning
confidence: 99%